Patients’ Experiences of a Nurse-Guided Physical Activity Program for Type 2 Diabetes and Its Perceived Impact on Health and Quality of Life: A Qualitative Descriptive Study - Jamal M. Alzahrani; Abdulaziz M. Alodhailah; Monirah Albloushi; Majed M. Aljabri; Mohammed Almutairi (Healthcare, 2026)
Background: Type 2 diabetes mellitus (T2DM) represents a significant global health challenge, with physical activity recognized as a cornerstone of effective disease management. Nurse-guided physical activity programs offer a promising approach to enhancing glycemic control and quality of life; however, patients’ lived experiences of such interventions remain underexplored, particularly in Middle Eastern contexts. Aim: To explore the perceived experiences of patients with T2DM participating in a nurse-guided physical activity program and understand its role in improving their health outcomes and quality of life. Methods: A qualitative descriptive design was employed. Sixteen adults with T2DM who completed a 12-week nurse-guided physical activity program were purposively recruited from multiple healthcare institutions in Saudi Arabia, including both public and private facilities. Semi-structured interviews were conducted using a 20-item interview guide. Data were analyzed using Braun and Clarke’s six-phase reflexive thematic analysis. Trustworthiness was ensured through member checking, peer debriefing, and maintaining an audit trail. The study adhered to the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. Results: Four overarching themes emerged: (1) Transformative Health Journey, encompassing perceived physiological improvements and enhanced energy levels; (2) Psychological Awakening, reflecting improved mood, self-efficacy, and reduced diabetes-related distress; (3) The Pivotal Role of Nursing Support, highlighting the significance of professional guidance, monitoring, and therapeutic relationships; and (4) Navigating Challenges and Charting Future Directions, addressing barriers, facilitators, and recommendations for program enhancement. Conclusions: Nurse-guided physical activity programs offer multidimensional benefits for patients with T2DM, extending beyond physiological improvements to encompass psychological well-being and lifestyle transformation. Nursing professionals play a critical role in motivating, educating, and supporting patients throughout their health journey. These findings support the integration of nurse-led physical activity interventions into routine diabetes care.